Pengelolaan Keuangan Berbasis Web PT. Mutualplus Global Resources Cabang Pontianak - Windi Irmayani; Yulia Yulia; Rahayu Dwi Utami (Jurnal Sistem Informasi Akuntansi, 2020)
PT. Mutualplus Global Resources Pontianak Sub Division consultant outsourcing company. According to the result of analysis found that processing the financial reports still using bookkeeping technique which is rewriting of notes to ledger and then converted to MS. Excel to be produced as financial reports, so the generated reports were late and not accurate. This Final Project contained about the research to solved the problems at PT. Mutualplus Global Resources by building the web-based of financial management accounting information system using waterfall model as software development method which consists of software requirement analysis, design, code generation and testing. The system is built to provides facilities for Admin & Finance and Directors. Admin and Finance can manage account data, cash receipt data, cash disbursement data, access general journals, ledgers, balance sheet reports, cash receipt reports, cash disbursement reports, income statements and statement of capital reports. Meanwhile, the Director can manage user data, access general journal reports, general ledger reports, balance sheet reports, cash receipts reports, cash disbursement reports, income statements and statement of capital reports. This system is expected to improve financial management performance at PT. Mutualplus Global Resources Pontianak sub Division.